Evidence-based traditional medicine for transforming global health and well-being: Bhushan Patwardhan1*, L. Susan Wieland2, Obijiofor Aginam3, Anchalee Chuthaputti4, Ricardo Ghelman5, Roshanak Ghods6, Goh Cheng Soon7, Motlalepula G. Matsabisa8, Georg Seifert9, Sione Tu'itahi10, Kim Sung Chol11, Shyama Kuruvilla12, Kathi Kemper13, Holger Cramer14, H.R. Nagendra15, Anup Thakar16, Tanuja Nesari17, Sanjeev Sharma18, Narayanam Srikanth19 and Rabinarayan Acharya20 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
In the current Anthropocene epoch, characterized by intensified, human-induced environmental crises, natural disasters the interconnectedness of human health and the health of the planet has become more evident with the resulting responsibility to promote healthy living conditions1. In our interconnected world, health challenges transcend borders, and addressing them necessitates comprehensive solutions that consider the complex interplay of factors influencing health outcomes. The COVID-19 pandemic has shown that current healthcare systems have limitations and vulnerabilities. This highlights the importance of adopting preventive and healthpromoting strategies that go beyond national boundaries. Concepts such as planetary health and One Health are emerging as integrated, unifying strategies to optimize the health of people, animals, plants, and the planetary ecosystem. To address the complex global challenges of the 21st century including: geopolitical conflicts, economic crises, environmental disasters, and pandemics, it is crucial to rethink healthcare. This reimagining is essential for successfully reaching the Sustainable Development Goals (SDGs) and creating a better and more sustainable future for everyone. It is critical to carefully address the social and environmental determinants of health beyond conventional notions of healthcare limited to sick care. is critical. Agreeably, healthcare must prioritize explicitly the well-being and prosperity of individuals and communities looking more broadly at social policies impacting health such as agriculture and food, transportation, city planning, housing, racism, sexism, gun safety, criminal justice, war and peace. Embracing principles such as Universal Health Coverage (UHC), preventive healthcare, multi-sectoral collaborations, social justice, environmental responsibility, and digital technology innovations can pave the way for more equitable and resilient societies.